Cerebellar hemorrhage in full-term neonate: a case report and literature review - Palić, Ilija; Kostić, Katarina; Vasiljević, Stevan (Medical Research, 2025)
Introduction/Objective: Cerebellar hemorrhage is a common condition in neonates born before 32th weeks of gestation, and it rarely occurs in full-term neonates. The most important risk factors for cerebellar hemorrhage in full-term neonates are traumatic delivery, instrumentation-assisted vaginal delivery, emergency cesarean section, perinatal asphyxia as well as perinatal infection.Patient Review: We present a case of cerebellar hemorrhage and cerebral edema in a neonate with culture-negative early-onset sepsis. A full-term male neonate born from uncontrolled pregnancy developed respiratory distress, as well as clinical and laboratory signs of sepsis. The neonate’s condition was complicated by respiratory failure, neurological deterioration and neonatal seizures. Chest radiography showed right-sided pneumonia and the head ultrasound showed cerebral edema and hemorrhage in right cerebellar hemisphere. Blood culture, tracheal aspirate and cerebrospinal fluid culture were sterile. The studies showed low incidence of blood culture confirmed early-onset sepsis due to high use of antibiotics in neonatal units. However, the course of the disease and the resulting complications suggest as a possible cause group B β-hemolytic Streptococcus, as the most common cause of early-onset sepsis in full-term neonates. Given the relationship between poor neurodevelopmental outcome in children and neonatal cerebellar hemorrhage, long-term follow-up by a pediatric neurologist is required.Conclusion: Despite the incidence of cerebellar hemorrhage in full-term neonates is low, due to the poor neurodevelopmental outcome, a head ultrasound through the “mastoid window” is advised in all critically ill neonates to detect cerebellar hemorrhage.
Keywords: cerebellar hemorrhage, brain edema, brain injury, newborn, sepsis